Assessment of total haemoglobin mass: can it detect erythropoietin-induced blood manipulations? - Lundby, C.; Robach, P. (European Journal of Applied Physiology, 2010)
The purpose of the study was to reveal erythropoietin (epo) doping. It was recently suggested that the assessment of total haemoglobin mass (tHb) by means of the carbon monoxide re-breathing technique should be implemented in anti-doping work. Since epo may increase the haemoglobin concentration [Hb] simply by reducing plasma volume we injected eight human subjects with epo for 15 weeks and directly tested the feasibility hereof. Epo treatment increased [Hb] in all subjects at all time points (range 3.8-18.8%). In approximately half the subjects this was mainly the consequence of an increased tHb, but in the remaining subjects the change was the result of a decrease in the plasma volume. After the initial epo "boosting" period the assessment of tHb could not detect epo injections in 50% of the subjects in the remaining "maintenance" period. In our opinion the variability observed over time when assessing tHb is not justifiable in an anti-doping setting.